2013
DOI: 10.1099/vir.0.058040-0
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule depolymerization activates the Epstein–Barr virus lytic cycle through protein kinase C pathways in nasopharyngeal carcinoma cells

Abstract: Elevated levels of antibodies against Epstein-Barr virus (EBV) and the presence of viral DNA in plasma are reliable biomarkers for the diagnosis of nasopharyngeal carcinoma (NPC) in highprevalence areas, such as South-East Asia. The presence of these viral markers in the circulation suggests that a minimal level of virus reactivation may have occurred in an infected individual, although the underlying mechanism of reactivation remains to be elucidated. Here, we showed that treatment with nocodazole, which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Liu et al . also recently reported that nocodazole, which could induce mitotic arrest in various types of cell lines, could reactivate EBV lytic cycle in NPC cells . The exact relationship of cell cycle arrest and lytic cycle reactivation in EBV‐positive cancer cells deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Liu et al . also recently reported that nocodazole, which could induce mitotic arrest in various types of cell lines, could reactivate EBV lytic cycle in NPC cells . The exact relationship of cell cycle arrest and lytic cycle reactivation in EBV‐positive cancer cells deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al also recently reported that nocodazole, which could induce mitotic arrest in various types of cell lines, could reactivate EBV lytic cycle in NPC cells. 39 The exact relationship of cell cycle arrest and lytic cycle reactivation in EBV-positive cancer cells deserves further investigation. To further evaluate the role of HDAC inhibition in the lytic reactivation by HDAC inhibitors, we performed shRNA knockdown experiments to specifically inhibit HDAC-1, -2 and -3.…”
Section: Discussionmentioning
confidence: 99%
“…The switch, marked by Zta expression, can be induced by active NF-κB and AP-1 through PKC. This report was followed by similar reports from other groups 36,37. The MAPK family consists of 3 member cascades, extracellular signal regulated kinases (ERKs), c-Jun NH 2 -terminal kinases (JNKs), and p38 and is usually activated as a partner of the PKC signaling pathway.…”
Section: Host Factors Contributing To the Regulation Of Ebv Reactimentioning
confidence: 66%
“…; Liu et al. ). Specifically tubulin and actin filaments are polymers made up of monomeric units and there is evidence that gene expression is actively regulated by the proportion of monomeric to polymeric actin and/or tubulin, raising the possibility that cytoskeletal polymerization status may be important in gene regulation in chondrocytes (Rosette & Karin, ; Hui et al.…”
Section: Introductionmentioning
confidence: 98%